PROBLEMS OF RISK COMMUNICATION RELATED TO THE PROVISION OF THE RADIATION SAFETY. BASIC CONCEPTS AND DEFINITIONS - L. V. Repin; A. M. Biblin; N. M. Vishnyakova (Радиационная гигиена, 2018)
The implementation of the State program of the Russian Federation “Development of nuclear power industry”, Federal target program «Ensuring Nuclear and Radiation Safety from 2016 to 2020 and up to 2030», introduction of new imaging modalities in medicine that are associated with high patient and staff doses, poor public awareness of the presence and level of hazard of natural sources of ionizing radiation determine the relevance of the current study. The aim of the study was to develop the effective methods of risk communication for the improvement of the radiation protection and safety of the population, to introduce these methods in the daily practice of Rospotrebnadzor and, eventually, to assist in the formation of a risk-oriented society in the Russian Federation. Currently, Russian-language terminology in the field of risk communication is not developed; Russian terms are frequently just poor adapted/translated versions of English terms. This manuscript is focused on the definition of the basic concepts of risk communication and the formation of uniform terminology in the field of the radiation safety of the population. A glossary of basic terms in the field of riskcommunication is attached to the manuscript. The authors, considering the analysis of scientific data, suggest the following definition of risk communication: a process of interaction with other participants that is intentionally initiated by one of the participants in the information field of risk and is aimed at the evaluation of the attitudes on risk, their formation or change in other participants; formation or change of own attitudes on risk.